Strategy for Implementing Organizational Culture in Companies and Their Impact on Work Motivation, Job Satisfaction, and Organizational Commitment - Charles Jonson Siregar; Widodo Sunaryo; Nancy Yusnita (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the relationship and interaction between work motivation, job satisfaction, and organizational commitment towards organizational culture. The research method uses a qualitative and quantitative approach, distributing questionnaires to respondents, which are then analyzed using descriptive statistics, correlation tests, mean difference tests, and ANOVA. The research results indicate that employee motivation, satisfaction, and commitment are at a fairly high level. The relationships between variables are positive, with the strongest correlation shown between job satisfaction and organizational commitment. ANOVA tests confirm the existence of significant interactions between motivation and satisfaction, as well as between satisfaction and commitment, but no simultaneous effect was found when all three variables were tested together. This finding confirms that job satisfaction plays a crucial role in creating a healthy organizational culture. A productive organizational culture can be built by strengthening work motivation, increasing satisfaction, and fostering commitment, especially by focusing on a combination of proven significant variables.